2001
DOI: 10.1523/jneurosci.21-10-03619.2001
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic Lesions of the Lateral Nucleus of the Amygdala Decrease Conditioned Fear But Not Unconditioned Fear of a Predator Odor: Comparison with Electrolytic Lesions

Abstract: Considerable evidence suggests that the lateral (LA) and basal (BA) nuclei of the amygdala are sites of plasticity and storage of emotional memory. Recent arguments, however, have seriously challenged this view, suggesting that the effects of amygdala lesions are attributable to interference with performance of fear behavior and not learning and memory. One way to address this controversy is to measure the same behavioral response during both conditioned and unconditioned fear. This is done in the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
3
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(114 citation statements)
references
References 64 publications
7
100
3
4
Order By: Relevance
“…Because muscimol works via GABA A receptors, fibers of passage are not inactivated. Therefore, the findings of the present study are in agreement with the explanation offered by Wallace and Rosen (2001). In addition, our study confirmed findings (Wallace and Rosen, 2001) that the lateral nucleus of the amygdala is not necessary for the production of freezing per se.…”
Section: Role Of the Amygdala In Tmt-induced Freezingsupporting
confidence: 93%
See 2 more Smart Citations
“…Because muscimol works via GABA A receptors, fibers of passage are not inactivated. Therefore, the findings of the present study are in agreement with the explanation offered by Wallace and Rosen (2001). In addition, our study confirmed findings (Wallace and Rosen, 2001) that the lateral nucleus of the amygdala is not necessary for the production of freezing per se.…”
Section: Role Of the Amygdala In Tmt-induced Freezingsupporting
confidence: 93%
“…This supports the results of Wallace and Rosen (2001) demonstrating an unimpaired freezing response to TMT after neurotoxic lesions of the amygdala. In that study, electrolytic lesions of the amygdala reduced or blocked TMT-induced freezing.…”
Section: Role Of the Amygdala In Tmt-induced Freezingsupporting
confidence: 90%
See 1 more Smart Citation
“…A previous report has shown that lesioning the BLA does not effect fear-related behavioral responses to fox odor (Wallace and Rosen, 2001); whereas, other studies demonstrate that lesioning and/or inactivating the BLA alters freezing in response to cat or fox odors (Vazdarjanova et al, 2001;Takahashi et al, 2005;Muller and Fendt, 2006). In addition, exposure to cat odor failed to increase BLA c-fos expression (Dielenberg et al, 2001), but in another study exposure to red fox odor increased BLA c-fos expression (Funk and Amir, 2000).…”
Section: Discussionmentioning
confidence: 81%
“…To examine innate fear, mice were placed in the chamber with a beaker containing 30 l of a synthetic fox feces odor, trimethylthiazoline (TMT; PheroTech), which was reported previously to elicit freezing in rodents (Wallace and Rosen, 2001). TMT-evoked freezing was recorded for 10 min after TMT exposure and scored as a percentage of the time spent in the freezing behavior at 2 min intervals.…”
Section: Methodsmentioning
confidence: 99%